Placental scaffolds have the ability to support adipose-derived cells differentiation into osteogenic and chondrogenic lineages - Baracho Trindade Hill, Amanda [UNESP]; Speri Alves, Antonio Alexandre; Silva Nunes Barreto, Rodrigo da; Fernandes Bressan, Fabiana; Miglino, Maria Angelica; Mansano Garcia, Joaquim [UNESP] (Wiley-Blackwell, 2020)
Prudent choices of cell sources and biomaterials, as well as meticulous cultivation of the tissue microenvironment, are essential to improving outcomes of tissue engineering treatments. With the goal of providing a high-quality alternative for bone and cartilage tissue engineering, we investigated the capability of bovine placental scaffolds to support adipose-derived cell differentiation into osteogenic and chondrogenic lineages. Decellularized bovine placenta, a high-quality scaffold with practical scalability, was chosen as the biomaterial due to its rich extracellular matrix, well-developed vasculature, high availability, low cost, and simplicity of collection. Adipose-derived cells were chosen as the cell source as they are easy to isolate, nontumorigenic, and flexibly differentiable. The bovine model was chosen for its advantages in translational medicine over the mouse model. When seeded onto the scaffolds, the isolated cells adhered to the scaffolds with cell projections, established cell-scaffold communication and proliferated while maintaining cell-cell communication. Throughout a 21-day culture period, osteogenically differentiated cells secreted mineralized matrix, and calcium deposits were observed throughout the scaffold. Under chondrogenic specific differentiation conditions, the cells modified their morphology from fibroblast-like to round cells and cartilage lacunas were observed as well as the deposit of cartilaginous matrix on the placental scaffolds. This experiment provides evidence, for the first time, that bovine placental scaffolds have the potential to support bovine mesenchymal stem cell adherence and differentiation into osteogenic and chondrogenic lineages. Therefore, the constructed material could be used for bone and cartilage tissue engineering.
Keywords: bone tissue engineering; cartilage tissue engineering; cows; decellularization; mesenchymal stem cells; placenta; recellularization; translational medicine